1999
DOI: 10.1177/019263659908360608
|View full text |Cite
|
Sign up to set email alerts
|

Who Will Lead? The Top 10 Factors That Influence Teachers Moving into Administration

Abstract: The top 10 factors that influence teachers who are applying for an administrative position describe a complex list of “wants and needs” for this new generation of school leaders. A study strongly suggests that organizational relationships, more than any other factors, affect a teacher's willingness to seek an administrative position in a particular district.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 1 publication
1
28
1
3
Order By: Relevance
“…This finding is in contrast to Cooley and Shen (1999) and Cusick (2003) who found that salary was one of the top factors that aspiring principal candidates consider when applying for an administrative position.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast to Cooley and Shen (1999) and Cusick (2003) who found that salary was one of the top factors that aspiring principal candidates consider when applying for an administrative position.…”
Section: Discussioncontrasting
confidence: 99%
“…Over 81% of the respondents indicated that the amount of support from the district office was the most important factor to consider when entering the principalship (Cooley and Shen 1999). According to Cusick (2003), principals in the Michigan study repeatedly stated that their district office does not support them in disputes with parents.…”
Section: Introductionmentioning
confidence: 99%
“…A desire to define leadership has dominated much of the leadership research, and the topic has been addressed in many studies and continues to be addressed today (e.g., Cooley and Shen, 1999;Portin, Shen and William, 1998;Shen, 2001;Rincones, 2002;Rodríguez, 2002;Weiss and Cambone, 1994). According to Owens (1998), no one of those definitions on leadership will satisfy everyone; however, those definitions generally agree on two things: (a) leadership is a group function, because it occurs only in the processes of two or more people interacting, and (b) leaders intentionally seek to influence the behavior of other people.…”
Section: 1mentioning
confidence: 99%
“…They trade in their 180-190 day work year for one that exceeds 220 days, take on enormous responsibilities and headaches, lose their job security, and earn just a little more or even less on a per diem basis than they would earn as teachers. While no one would dispute that teachers should be better paid, this compression of salaries has led to a very small differential between teachers and principals and between central office employees and superintendents (Cooley & Shen, 1999;Houston, 1998).…”
Section: Low Compensation/salariesmentioning
confidence: 99%
“…Emotional aspects related to administration include stress, burnout, and frustration. Cooley and Shen (1999) found that more than 65% of teachers responding to their survey suggested that the emotional aspects of administration were a major consideration in applying for an administrative position. Seventy-two percent of respondents stated that they would consider the impact of administration on their home life when applying for an administrative position.…”
Section: Stress In School Administrationmentioning
confidence: 99%